On female technology or Femtech. Artificial intelligence, women’s health and the will of the individual (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Taking the Femtech phenomenon as a starting point, this contribution examines aspects of the use of artificial intelligence by women’s health technologies. In particular, the issues of algorithmic discrimination and automated decision-making based on health-related data are considered. The critical analysis of the provisions of European Union law is conducted, in the awareness of the fruitfulness of the solutions offered by technology itself (e.g. synthetic data), seeking a systemic solution that can offer protection in the concrete and specific situation of the subject. In this sense, the reflection proposes a valorisation of the individual’s will, in the light of the values of the person and his dignity.
Keywords: Femtech; artificial intelligence; health data; personal rights; will